2019
DOI: 10.1556/650.2019.31258
|View full text |Cite
|
Sign up to set email alerts
|

Kiégés és reziliencia (rugalmas ellenállás) a magyarországi orvosok körében

Abstract: Introduction: The burnout of healthcare workers is of outstanding significance in both national and international studies. Aim: Based on a representative, national physician survey (n = 5013), the aim of this study was to describe burnout indicators and the correspondence between them and working conditions. Moreover, we were aiming to compare the results with our 2013 physician survey and to analyze the potential relationship between burnout and resilience. Method: We analyzed the results of the online quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
5
1
1
Order By: Relevance
“…The prevalence of burnout in current study is higher, than previously reported in general sample of the Hungarian healthcare professionals [32]. Participants exhibit moderate burnout on all three scales, although the depersonalization results seem to be on the border between moderate and low.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The prevalence of burnout in current study is higher, than previously reported in general sample of the Hungarian healthcare professionals [32]. Participants exhibit moderate burnout on all three scales, although the depersonalization results seem to be on the border between moderate and low.…”
Section: Discussioncontrasting
confidence: 81%
“…Even though the Central European region is underrepresented in burnout research, there have been some studies on burnout syndrome executed on Hungarian samples [6,[31][32][33], which partially mapped out the occurrence, background factors and risk factors of burnout syndrome among general practitioners, medical students or female physicians [7,31,34]. These studies confirm the relationship between work stress, physical and emotional burden and burnout, and define the emotional exhaustion, depersonalization, depletion of performance, poor relationship with colleagues and lack of communication to be key factors contributing to higher levels of burnout [6,[31][32][33]. There is so far no data on relationship between the psychological immune competency and burnout syndrome among employees of emergency departments, intensive care units or surgery departments, which is particularly important, as these healthcare professionals are working in high-stress environments.…”
Section: Introductionmentioning
confidence: 99%
“…Our study was conducted in Hungary, in Central-Europe. Recent studies suggest that burnout and emotional exhaustion appear to be moderate to severe in a significant proportion of Hungarian helping professionals (Győrffy, 2019;Mák et al, 2020). We believe that our results are relevant beyond Hungary, as our study is the first to examine the constellation of these variables.…”
Section: Vital Exhaustion Andmentioning
confidence: 56%
“…The connection between burnout and resilience was confirmed. According to the research of Győrffy (2019) , results have shown that internal resources, coping strategies and resilience play a crucial role in burnout and its decrease.…”
Section: Resultsmentioning
confidence: 99%